2017
DOI: 10.1016/j.ejvs.2016.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Variations of Flow to Renal Arteries in Custom-Made and Pivot Branch Fenestrated Endografting

Abstract: Navigating the renal stents towards caudal orientation can achieve better haemodynamic outcomes in both fenestrated devices. Custom-made fenestrated stent grafts are the preferred choice for elective patients. Further clinical evidence is required to validate the computational simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…In the vast majority of CFD studies, the EVAR devices are simulated with an unwrinkled fabric surface that serves as a smooth boundary wall for the blood flow. 20,22,34,35 Yet by disregarding the wrinkles on the surface of the graft, possible flow disturbances can be overlooked. Herein, it was successfully demonstrated that the output of the FEA simulation can be used as input for a CFD investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the vast majority of CFD studies, the EVAR devices are simulated with an unwrinkled fabric surface that serves as a smooth boundary wall for the blood flow. 20,22,34,35 Yet by disregarding the wrinkles on the surface of the graft, possible flow disturbances can be overlooked. Herein, it was successfully demonstrated that the output of the FEA simulation can be used as input for a CFD investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previous ideal model used to study branched stent configurations 17,33,38 , the models used in this study were derived from clinical cases, which examined and added the current knowledge with "real-world" data. Moreover, the models in this study provided important insights on the velocity and the WSS distribution of the BSG.…”
Section: Discussionmentioning
confidence: 99%
“…This failure of correlation even remains true when hemodynamic outcomes are improved with caudal orientation of renal stents. 20 Thus, despite much suspicion that forced anatomic changes may bear some culpability for the deterioration of renal function often seen after aneurysm repair, contemporary imaging techniques have failed to provide proof. We believe a functional indicator, such as renal volume, which links anatomic change to important perfusion-related outcomes, provides a surrogate measure of stent performance, and may be a better indicator of the four-dimensional behaviour of the stents.…”
Section: Discussionmentioning
confidence: 99%